Synthesis and Study of Oxygen Bridged Liquid Crystalline Copolyesters - Roopsingh, D.; Malathy, N.; Sathyamurthy, P.; Kannappan, V. (Asian Journal of Chemistry, 2010)
Six new thermotropic liquid crystalline random copolyesters with ethereal linkages were prepared from mesogenic 4,4'-oxybis(benzoic acid) by direct polycondensation with different aromatic diols in pyridine solution. Diphenylchlorophosphate (DPCP) was employed as the condensation agent. The solution viscosity numbers ranged from 0.41-0.81 dL/g. The glass transition temperature of these polymers were determined by thermal studies (DSC and optical polarizing microscopy) and found to lie between 41.4 and 61.5 ºC. Spectral studies (1H, 13C NMR and FT IR) gave an insight about the microstructure and copolymer compositions. The polyester composite film was exposed to UV irradiation to find changes in morphology by SEM analysis.